Interaction of gut microbiota with the tumor microenvironment: A new strategy for antitumor treatment and traditional Chinese medicine in colorectal cancer - Li, Tingting; Han, Liang; Ma, Simin; Lin, Weiji; Ba, Xin; Yan, Jiahui; Huang, Ying; Tu, Shenghao; Qin, Kai (Frontiers in Molecular Biosciences, 2023)
Colorectal cancer (CRC) is one of the most common malignancies worldwide and the second leading cause of cancer-related death. In recent years, the relationship between gut microbiota and CRC has attracted increasing attention from researchers. Studies reported that changes in the composition of gut microbiota, such as increase in the number of Fusobacterium nucleatum and Helicobacter hepaticus, impair the immune surveillance by affecting the intestinal mucosal immunity and increase the risk of tumor initiation and progression. The tumor microenvironment is the soil for tumor survival. Close contacts between gut microbiota and the tumor microenvironment may directly affect the progression of tumors and efficacy of antitumor drugs, thus influencing the prognosis of patients with CRC. Recently, many studies have shown that traditional Chinese medicine can safely and effectively improve the efficacy of antitumor drugs, potentially through remodeling of the tumor microenvironment by regulated gut microbiota. This article describes the effect of gut microbiota on the tumor microenvironment and possible mechanisms concerning the initiation and progression of CRC, and summarizes the potential role of traditional Chinese medicine.